2015
DOI: 10.3390/w7094638
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Scale Approach in Hydraulic Characterization of a Metamorphic Aquifer: What Can Be Inferred about the Groundwater Abstraction Possibilities

Abstract: Hard-rock aquifers, which constitute a water supply source in many countries, are highly heterogeneous and defining a realistic model of an aquifer can be extremely complex. The objective of this study was to hydraulically characterize a metamorphic aquifer in a representative area of Italy and to identify the most appropriate approach for tapping of groundwater in this challenging environment. The results of surface fracture surveys, injection tests, pumping tests, and a simplified numerical model were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Several tens of wells drilled in the fissured layer Special Issue AQUA2015 -DOI: 10.7343/as-2016-195 of granitoid rocks (and in some cases also including their weathered mantle) show yields between 0.1 and 2 L/s, values of transmissivity between 10 -6 and 10 -4 m 2 /s and of storativity between 0.05 and 2 % (Barrocu 2003;2007). In Southern Sardinia, some wells drilled near a faulted zone in the fissured layer of low-grade metamorphic rocks show yields between 1 and 3 L/s, values of transmissivity between 10 -4 and 10 -3 m 2 /s and of storativity between 0.03 and 3 % (Baiocchi et al 2015). At present, only about thirty springs (Fig.…”
Section: Current Knowledge About Occurrence and Flow Of Groundwater In Crystalline Rocksmentioning
confidence: 96%
See 1 more Smart Citation
“…Several tens of wells drilled in the fissured layer Special Issue AQUA2015 -DOI: 10.7343/as-2016-195 of granitoid rocks (and in some cases also including their weathered mantle) show yields between 0.1 and 2 L/s, values of transmissivity between 10 -6 and 10 -4 m 2 /s and of storativity between 0.05 and 2 % (Barrocu 2003;2007). In Southern Sardinia, some wells drilled near a faulted zone in the fissured layer of low-grade metamorphic rocks show yields between 1 and 3 L/s, values of transmissivity between 10 -4 and 10 -3 m 2 /s and of storativity between 0.03 and 3 % (Baiocchi et al 2015). At present, only about thirty springs (Fig.…”
Section: Current Knowledge About Occurrence and Flow Of Groundwater In Crystalline Rocksmentioning
confidence: 96%
“…Current knowledge on the hydrogeology of the crystalline rocks of Sardinia and Calabria is scarce. General considerations on occurrence of groundwater flow and some studies limited to specific areas are reported in the scientific and technical literature (e.g., Celico et al 2000;Barrocu 2003;Allocca et al 2006;Regione Autonoma della Sardegna 2006a;2006b;Barrocu 2007;Regione Calabria 2008;Baiocchi et al 2014;Baiocchi et al 2015).…”
Section: Current Knowledge About Occurrence and Flow Of Groundwater In Crystalline Rocksmentioning
confidence: 99%
“…1, the dam is located at the transition area where the Paleozoic basement is related to the Hercynian orogenic evolution outcrops. The Paleozoic basement consists of an originally sedimentary succession (Lower Cambrian to Early Carboniferous) that was deformed during the Carboniferous period under the low metamorphic to anchizonal setting (20,21). The Arburese Unit outcropping at the dam site consists of the Arenarie di San Vito Formation (Middle Cambrian to Lower Fig.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Ordovician), which is several hundred metres thick and is composed of decametric to metric alternations between micaceous metasandstones, quartzites and metasiltstones. Clastic, poorly cemented sediments, from gravels to sands and silts, of the Upper Pleistocene to the Holocene overlay the metamorphic basement (21).…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation